Forefront of Na+/Ca2+ Exchanger Studies: Regulation Kinetics of Na+/Ca2+ Exchangers - Satoshi Matsuoka (Journal of Pharmacological Sciences, 2004)
Five isoforms of Na+/Ca2+ exchanger have been identified: NCX1, NCX2, NCX3, NCX-SQ1, and CALX. In all of the exchangers, the Na+/Ca2+ exchange current, which was recorded in inside-out membrane patches, was regulated by cytoplasmic Ca2+. However, the mode of regulation is different among the exchangers. NCX1, NCX2, and NCX-SQ1 are positively regulated by cytoplasmic Ca2+, but CALX is negatively regulated. NCX3 apparently has both positive and negative regulation mechanisms. In this review, I briefly summarize the Ca2+-dependent regulation mechanisms of the exchangers. Keywords:: Na+/Ca2+ exchanger (NCX), transporter, regulation, patch clamp